Pembuatan Video Promosi Agrowisata Swargo Tani Menggunakan Metode Color Grading Dalam Teknik Editing - Septi Widya Rani Rahayu; Agusdi Syafrizal; Subhan Hartanto (CV MEDAN TEKNO SOLUSI, 2026)
Swargo Tani Agrotourism is a rural farming destination located in Kutai Kartanegara. Despite its potential, ineffective promotional strategies hinder public engagement. This study aims to develop a promotional video using editing techniques, particularly color grading, to improve visual appeal and message delivery. The project follows four stages:pre-production, production, post-production, and distribution. Color grading is applied to balance tones and enhance natural visuals such as green vegetation and blue skies. The video is published via digital platforms and effectively attracts more attention. The findings indicate that applying color grading enhances video quality and effectiveness in promoting local agrotourism.